2020
DOI: 10.3390/app10093254
|View full text |Cite
|
Sign up to set email alerts
|

Study on Passenger Comfort Based on Human–Bus–Road Coupled Vibration

Abstract: Nowadays, the comfort of drivers and passengers is drawing more and more attention. The interaction between vehicles and the asphalt road can cause coupled vibration and reduce the comfort of passengers. Therefore, the research on human–vehicle–road coupled vibration and the comfort of passengers is of great importance. In this paper, the three-dimensional human–bus–road coupled vibration system is established, including the bus model, the parallel biomechanical human model with 2 degrees-of-freedom (DOF), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This shows that the random vibration caused by vehicle–road coupling can spread along the road and affect the surrounding infrastructure [ 14 ]. This point is also mentioned in the research of Arabi [ 15 ] and Wang [ 16 ] through the establishment of a three-dimensional human–bus–road coupling vibration system; the analysis shows that the road vibration can affect human comfort. Currently, the main research direction of vehicle–road coupling vibration focuses on the damage of vehicle–road action on asphalt pavement and adjacent buildings, along with the influence of such vibrations on pedestrian comfort.…”
Section: Introductionmentioning
confidence: 77%
“…This shows that the random vibration caused by vehicle–road coupling can spread along the road and affect the surrounding infrastructure [ 14 ]. This point is also mentioned in the research of Arabi [ 15 ] and Wang [ 16 ] through the establishment of a three-dimensional human–bus–road coupling vibration system; the analysis shows that the road vibration can affect human comfort. Currently, the main research direction of vehicle–road coupling vibration focuses on the damage of vehicle–road action on asphalt pavement and adjacent buildings, along with the influence of such vibrations on pedestrian comfort.…”
Section: Introductionmentioning
confidence: 77%
“…where the meaning of the subscript i and j is the same as that of the equation (13). K ij denotes the axis weighting factors and a 0 is the RMS value of the reference acceleration, that is, a 0 � 10 −6 m/s 2 .…”
Section: New Methods For Evaluating Driving Comfortmentioning
confidence: 99%
“…Furthermore, variations in vibrations exist between the driver and the vehicle body, a facet not adequately addressed by current driving comfort assessment standards [11]. In recent years, scholars have delved into comprehensive research on interaction analysis models for passenger-vehicle-railway bridge systems [12,13]. For example, Wang et al simplifed passengers as a fve-degree-of-freedom spring-damping model, conducting a comparative analysis of passenger and train dynamic responses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have also researched the impact of road excitation on driver comfort. Wang et al (2020) analyzed the effects of pavement roughness, interlayer bonding conditions, bus weight, bus speed, and seating on human comfort. They concluded that pavement roughness had the greatest impact on human comfort.…”
Section: Introductionmentioning
confidence: 99%